Hepatoprotective effect of diallyl trisulfide against lipopolysaccharide and D-galactosamine induced acute liver failure in mice via suppressing inflammation and apoptosis. Issue 2 (19th February 2022) - Yu, Ziqiang; Ding, Yun; Zeng, Tao; Zhao, Xiulan; Zhang, Cuili
Abstract: Acute liver failure (ALF), characterized by the quick occurrence of disorder in liver, is a serious liver injury with extremely high mortality. Therefore, we investigated whether diallyl trisulfide (DATS), a natural product from garlic, protected against ALF in mice and studied underlying mechanisms. In the present study, lipopolysaccharide (LPS) (10 μg·kg −1 )/D-galactosamine (D-gal) (500 mg·kg −1 ) was intraperitoneally injected to ICR mice to induce ALF. The mice were orally administered 20-, 40-, or 80-mg·kg −1 DATS) 1 h before LPS/D-gal exposure. Serum biochemical analyses and pathological study found that DATS pretreatment effectively prevented the ALF in LPS/D-gal-treated mice. Mechanistically, pretreatment of DATS inhibited the increase of the numbers of CD11b + Kupffer cells and other macrophages in the liver, the release of tumor necrosis factor-α into the blood, and Caspase-1 activation induced by LPS/D-gal treatment in mice. Furthermore, DATS inhibited the activation of Caspase-3, downregulation of Bcl-2/Bax ratio, and increase of TUNEL positive staining. Altogether, our findings suggest that DATS exhibits hepatoprotective effects against ALF elicited by LPS/D-gal challenge, which probably associated with anti-inflammation and anti-apoptosis.